Heat and Mass Transfer in a High-Porous Low-Temperature Thermal Insulation in Real Operating Conditions - Polovnikov V. Yu. Vyacheslav Yurievich; Habibulin A. M. Artem; Arkhipov V. A. Vladimir; Zharova I. K. Irina (2015, 2015)
Title screen